Exploring the links between psychological flexibility, individual well‐being, and relationship quality. Issue 4 (9th November 2020) - Twiselton, Karen; Stanton, Sarah C. E.; Gillanders, David; Bottomley, Ewan
Abstract: The ability to engage flexibly with thoughts and behavior in line with the demands of a situation—termed psychological flexibility —has been linked to individual well‐being. This registered report presents two studies that investigate the links between psychological flexibility, individual well‐being, and relationship quality. Using structural equation modeling, Study 1 found that people who were more psychologically flexible reported higher levels of positive affect and lower levels of negative affect, which in turn were associated with higher relationship quality. Using dyadic mediation analysis, Study 2 replicated and extended these findings in a sample of 200 romantic couples, revealing both actor and partner effects. This research offers insight into the implications of psychological flexibility for relationship functioning.